Piezoelectric laminate, piezoelectric element, and method for manufacturing piezoelectric laminate
By controlling the grain standard deviation of the potassium sodium niobate piezoelectric film and adding Cu and Mn elements, the environmental pollution problems of lead-based piezoelectric materials and the insufficient improvement of KNN performance are solved, and a longer service life and higher material stability are achieved.
Patent Information
- Application Number
- JP2019143327
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-08-02
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2039-08-02
AI Technical Summary
The existing lead-based piezoelectric materials have pollution problems in environmental protection, and the performance improvement of traditional potassium-sodium niobate (KNN) piezoelectric bodies is limited, making it difficult to meet further performance needs.
A piezoelectric film is used to optimize grain distribution and add copper (Cu) and manganese (Mn) elements by controlling the standard deviation of grain size to 0.42 μm or less, thereby improving the uniformity and stability of the film.
It extends the service life of the potassium sodium niobate piezoelectric film, improves the mobility and electrical insulation of the anti-oxidation defects, reduces the leakage current density, and enhances the reliability and etch resistance of the material.
Smart Images

Figure 0007626383000001 
Figure 0007626383000002 
Figure 0007626383000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a piezoelectric laminate, a piezoelectric element, and a method for manufacturing a piezoelectric laminate. [Background technology]
[0002] Piezoelectric materials are widely used in functional electronic components such as sensors and actuators. Piezoelectric materials include lead-based materials, especially those with the composition formula Pb(Zr 1-x Ti x PZT-based ferroelectrics represented by the formula (1) and (2) are widely used. PZT-based piezoelectric materials contain lead, which is undesirable from the standpoint of pollution prevention. Therefore, potassium sodium niobate (KNN) has been proposed as a lead-free piezoelectric material (see, for example, Patent Documents 1 and 2). In recent years, there has been a strong demand for further improving the performance of piezoelectric materials made of lead-free materials such as KNN. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2007-184513 A [Patent Document 2] JP 2008-159807 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to further extend the life of a piezoelectric film made of an alkali niobium oxide. [Means for solving the problem]
[0005] According to one aspect of the present invention, A substrate; An electrode film; Composition formula (K 1-x Na x)A piezoelectric laminate comprising a piezoelectric film made of an alkali niobate oxide having a perovskite structure represented by NbO3(0 < x < 1), and There is provided a piezoelectric laminate in which the standard deviation of the crystal grain size of the crystal constituting the piezoelectric film is 0.42 μm or less, and related technologies thereof.
Effects of the Invention
[0006] According to the present invention, it is possible to further extend the life of the piezoelectric film made of alkali niobate oxide.
Brief Description of the Drawings
[0007] [Figure 1] It is a diagram showing an example of a cross-sectional structure of a piezoelectric laminate according to an embodiment of the present invention. [Diagram 2] It is a diagram showing a modified example of a cross-sectional structure of a piezoelectric laminate according to an embodiment of the present invention. [Diagram 3] It is a diagram showing an example of a schematic configuration of a piezoelectric device according to an embodiment of the present invention. [Figure 4] It is a diagram showing an example of a cross-sectional structure of a piezoelectric laminate according to another embodiment of the present invention. [Diagram 5] It is a diagram showing a schematic configuration of a piezoelectric device according to another embodiment of the present invention.
Modes for Carrying Out the Invention
[0008] <An Embodiment of the Present Invention> Hereinafter, an embodiment of the present invention will be described with reference to the drawings.
[0009] (1) Configuration of the piezoelectric laminate As shown in FIG. 1, a laminate (laminated substrate) 10 having a piezoelectric film according to this embodiment (hereinafter also referred to as a piezoelectric laminate 10) includes a substrate 1, a lower electrode film 2 formed on the substrate 1, a piezoelectric film (piezoelectric thin film) 3 formed on the lower electrode film 2, and an upper electrode film 4 formed on the piezoelectric film 3.
[0010] As the substrate 1, a single crystal silicon (Si) substrate 1a on which a surface oxide film (SiO2 film) 1b such as a thermal oxide film or a CVD (Chemical Vapor Deposition) oxide film is formed, that is, a Si substrate having a surface oxide film, can be suitably used. As the substrate 1, as shown in FIG. 2, a Si substrate 1a having an insulating film 1d formed on its surface from an insulating material other than SiO2 can also be used. As the substrate 1, a Si substrate 1a on which a Si(100) face or a Si(111) face or the like is exposed on the surface, that is, a Si substrate having no surface oxide film 1b or insulating film 1d can also be used. As the substrate 1, a SOI (Silicon On Insulator) substrate, a quartz glass (SiO2) substrate, a gallium arsenide (GaAs) substrate, a sapphire (Al2O3) substrate, a metal substrate formed from a metal material such as stainless steel (SUS) can also be used. The thickness of the single crystal Si substrate 1a can be, for example, 300 to 1000 μm, and the thickness of the surface oxide film 1b can be, for example, 1 to 4000 nm.
[0011] The lower electrode film 2 can be formed using, for example, platinum (Pt). The lower electrode film 2 is a single crystal film or a polycrystalline film (hereinafter, these are also referred to as Pt film). It is preferable that the crystals constituting the Pt film are preferentially oriented in the (111) plane direction with respect to the surface of the substrate 1. In other words, it is preferable that the surface of the Pt film (the surface serving as the base of the piezoelectric film 3) is mainly composed of the Pt (111) plane. The Pt film can be formed using a method such as sputtering or vapor deposition. The lower electrode film 2 can also be formed using various metals such as gold (Au), ruthenium (Ru), or iridium (Ir), alloys mainly composed of these metals, metal oxides such as strontium ruthenate (SrRuO3, abbreviated as SRO) or lanthanum nickelate (LaNiO3, abbreviated as LNO), etc., other than Pt. In order to enhance adhesion between the substrate 1 and the lower electrode film 2, an adhesion layer 6 mainly composed of, for example, titanium (Ti), tantalum (Ta), titanium oxide (TiO2), nickel (Ni), ruthenium oxide (RuO2), iridium oxide (IrO2), or the like may be provided between the substrate 1 and the lower electrode film 2. The adhesion layer 6 can be formed by a method such as sputtering or vapor deposition. The thickness of the lower electrode film 2 can be, for example, 100 to 400 nm, and the thickness of the adhesion layer 6 can be, for example, 1 to 200 nm.
[0012] The piezoelectric film 3 contains, for example, potassium (K), sodium (Na), and niobium (Nb) and has a composition formula (K 1-x Na x)A film can be formed using an alkali niobate oxide represented by NbO3, that is, potassium sodium niobate (KNN). The coefficient x [=Na / (K+Na)] in the above composition formula shall be in the range of 0 < x < 1. The piezoelectric film 3 is a polycrystalline film of KNN (hereinafter also referred to as the KNN film 3). The crystal structure of KNN is a perovskite structure. The KNN film 3 may contain substances other than K, Na, and Nb. Here, a film with a composition of 90% or more of K, Na, and Nb is defined as the KNN film 3. Examples of substances other than K, Na, and Nb include calcium zirconate (CaZrO3, abbreviation: CZO), barium zirconate (BaZrO3, abbreviation: BZO), etc. The KNN film 3 can be formed using techniques such as sputtering, PLD (Pulsed Laser Deposition), and sol-gel methods. The thickness of the KNN film 3 can be, for example, 0.5 to 5 μm.
[0013] The crystals constituting the KNN film 3 are preferably preferentially oriented in the (001) plane orientation with respect to the surface of the substrate 1 (when the substrate 1 is, for example, a Si substrate 1a having a surface oxide film 1b or an insulating film 1d, etc., it is the Si substrate 1a). That is, the surface of the KNN film 3 (the surface that serves as the base for the upper electrode film 4) is preferably mainly composed of the KNN (001) plane orientation. By directly forming the KNN film 3 on a Pt film preferentially oriented in the (111) plane orientation with respect to the surface of the substrate 1, it becomes easy to preferentially orient the crystals constituting the KNN film 3 in the (001) plane orientation with respect to the surface of the substrate 1. For example, it becomes easy to orient 80% or more of the crystal group constituting the KNN film 3 in the (001) plane orientation with respect to the surface of the substrate 1, and to make 80% or more of the region of the surface of the KNN film 3 the KNN (001) plane.
[0014] It is preferable that more than half of the crystals in the crystal group constituting the KNN film 3 have a columnar structure. In addition, it is preferable that the boundaries between the crystals constituting the KNN film 3, i.e., the crystal grain boundaries present in the KNN film 3, run through the thickness direction of the KNN film 3. For example, it is preferable that the number of crystal grain boundaries running through the thickness direction of the KNN film 3 is greater than the number of crystal grain boundaries that do not run through the thickness direction of the KNN film 3 (for example, crystal grain boundaries parallel to the planar direction of the substrate 1).
[0015] The standard deviation of the grain size of the (each) crystal constituting the KNN film 3 (hereinafter also simply referred to as the "KNN crystal grain size") is 0.42 μm or less, preferably less than 0.3 μm. The smaller the standard deviation of the KNN crystal grain size (hereinafter also referred to as the "standard deviation of the KNN film 3"), the more preferable it is. There is no particular limit to the lower limit of the standard deviation of the KNN film 3, but the standard deviation of the KNN film 3 cannot be 0 (zero).
[0016] It is possible to reduce the standard deviation of the KNN film 3 by setting the initial film-forming rate faster than the later film-forming rate when forming the KNN film 3. By setting the initial film-forming rate to, for example, more than 2 μm / hr and 6 μm / hr or less, preferably 3 μm / hr or more and 5 μm / hr or less, and the later film-forming rate to, for example, 0.5 μm / hr or more and 2 μm / hr or less, preferably 0.5 μm / hr or more and 1.5 μm / hr or less, more preferably 0.5 μm / hr or more and 1 μm / hr or less, it is possible to set the standard deviation of the KNN film 3 to 0.42 μm or less, preferably less than 0.3 μm.
[0017] The initial film formation speed refers to the film formation speed in an initial stage of film formation of the KNN film 3. The initial film formation stage refers to a nucleation stage in which KNN nuclei (KNN crystal nuclei) are formed on the lower electrode film 2 (the base of the KNN film 3). The initial film formation stage refers to a period of 3 to 5 minutes from the start of film formation of the KNN film 3. The later film formation speed refers to the film formation speed in a later stage of film formation of the KNN film 3. The later film formation stage refers to a nucleus growth stage, which is a stage later than the initial film formation stage and in which the nuclei formed in the initial film formation stage are grown to form the KNN film 3.
[0018] By increasing the film formation speed (i.e., the initial film formation speed) during nucleus formation, it is possible to increase the number of nuclei generated (increase the nucleus density) on the lower electrode film 2. In other words, by increasing the film formation speed during nucleus formation, it is possible to form nuclei densely on the lower electrode film 2 (so that the nuclei are spread out over the lower electrode film 2).
[0019] By forming the nuclei densely in the early stages of film formation, the difference in size of the nuclei can be made smaller (the nuclei can be made uniform in size) compared to when the nuclei are formed sparsely (nuclei are formed so that the nuclei density is low). This allows the size of each crystal grain constituting the KNN film 3 to be uniform. In other words, the standard deviation of the KNN film 3 can be reduced.
[0020] Furthermore, by forming the nuclei densely, the nuclei can be formed uniformly on the lower electrode film 2. In other words, by forming the nuclei densely, it is possible to prevent the nuclei from concentrating locally on the lower electrode film 2. When the nuclei are formed locally, the crystal grain size of KNN becomes small in the part on the lower electrode film 2 where the nuclei are locally formed, and the crystal grain size of KNN becomes large in other parts on the lower electrode film 2. This results in the crystal grain size of KNN varying. By forming the nuclei uniformly on the lower electrode film 2, the variation in the grain size of the KNN crystals can be suppressed, and the size of each crystal grain constituting the KNN film 3 can be made uniform, thereby reducing the standard deviation of the KNN film 3.
[0021] Furthermore, by forming nuclei densely in the early film-forming stage, it is also possible to suppress the formation of nuclei in the later film-forming stage in areas where nuclei have not yet been formed on the lower electrode film 2. The nuclei formed in the later film-forming stage grow to fill in the gaps between the nuclei formed in the early film-forming stage and that have already started to grow. For this reason, the crystal grain size of KNN grown from the nuclei formed in the later film-forming stage is smaller than the crystal grain size of KNN grown from the nuclei formed in the early film-forming stage. By suppressing the formation of nuclei in the later film-forming stage, it is possible to make the sizes of the crystal grains constituting the KNN film 3 uniform and reduce the standard deviation of the KNN film 3.
[0022] The average grain size of the crystals (crystal group) constituting the KNN film 3 (hereinafter also referred to as the "average grain size of the KNN film 3") can be, for example, 0.1 μm to 1.0 μm, preferably 0.3 μm to 0.5 μm. The average grain size of the KNN film 3 here refers to the average grain size in the cross section of the KNN film 3 in the planar direction of the substrate 1. The average grain size of the KNN film 3 can be obtained by image analysis of the field of view of an image taken by a scanning electron microscope (e.g., an SEM image) or an image taken by a transmission electron microscope (e.g., a TEM image). As the image analysis software, for example, "ImageJ" made by Wayne Rasband can be used.
[0023] By making the average grain size of the KNN film 3 0.1 μm or more, it is possible to reduce the number of crystal grain boundaries present in the KNN film 3. In other words, it is possible to lower the grain boundary density of the KNN film 3. By making the average grain size of the KNN film 3 0.3 μm or more, it is possible to reliably lower the grain boundary density of the KNN film 3. Note that the grain boundary density here is the value obtained by dividing the total length of the crystal grain boundaries in the cross section of the KNN film 3 in the planar direction of the substrate 1 by the cross-sectional area of the cross section of the KNN film 3 (=total length of the crystal grain boundaries / cross-sectional area of the KNN film 3).
[0024] A certain ratio of oxygen vacancies (oxygen vacancies) exists inside the crystals (crystal grains) constituting the KNN film 3 and on the grain boundaries of the KNN film 3. The oxygen vacancies on the grain boundaries of the KNN film 3 may move, for example, when an electric field is applied to the KNN film 3. When the oxygen vacancies move and reach the electrode film (lower electrode film 2 or upper electrode film 4), they react with the metal contained in the electrode film, causing a short circuit. By lowering the grain boundary density of the KNN film 3, it is possible to reduce the ratio of oxygen vacancies on the grain boundaries of the KNN film 3 to the total oxygen vacancies present in the KNN film 3 (=(oxygen vacancies on the grain boundaries of the KNN film 3 / total oxygen vacancies present in the KNN film 3)×100). This makes it possible to reduce the oxygen vacancies that move toward the electrode film when an electric field is applied, and as a result, to extend the life of the KNN film 3.
[0025] From the viewpoint of reducing the grain boundary density of the KNN film 3, the larger the average grain size of the KNN film 3, the more preferable it is. However, in order to increase the average grain size of the KNN film 3, it is necessary to form nuclei sparsely on the lower electrode film 2, that is, to form nuclei on the lower electrode film 2 so as to reduce the nucleus density.
[0026] When the nuclei are formed sparsely, the size of the nuclei is more likely to vary (the size of the nuclei is more likely to vary) than when the nuclei are formed densely. In this case, the nuclei may be formed locally on the lower electrode film 2. In this case, the nuclei formed in the early stage of film formation may start to grow in the later stage of film formation, while nuclei may be formed in other parts of the lower electrode film 2 where no nuclei have been formed. As a result, when the nuclei are formed sparsely, the sizes of the crystal grains constituting the KNN film 3 may not be uniform. In this way, when the average grain size of the KNN film 3 (the grain size of the KNN crystal grains) becomes large, the standard deviation of the KNN film 3 may become large.
[0027] By setting the average grain size of the KNN film 3 to 1.0 μm or less, it is possible to reliably obtain a KNN film 3 having a standard deviation of 0.42 μm or less. By setting the average grain size of the KNN film 3 to 0.5 μm or less, it is possible to reliably obtain a KNN film 3 having a standard deviation of less than 0.30 μm.
[0028] The KNN film 3 preferably contains a metal element selected from the group consisting of copper (Cu) and manganese (Mn) at a concentration in the range of, for example, 0.2 at% to 2.0 at%. When both Cu and Mn are added to the KNN film 3, Cu and Mn are added to the KNN film 3 so that the total concentration of Cu and Mn is within the above-mentioned concentration range.
[0029] Adding at least one of Cu and Mn within the above-mentioned concentration range to the KNN film 3 can improve the film characteristics of the KNN film 3. For example, it can improve the insulation (leak resistance) of the KNN film 3 and set the relative dielectric constant of the KNN film 3 to a suitable value according to the application of the piezoelectric laminate 10.
[0030] For example, when the total concentration of Cu and Mn in the KNN film 3 is within the above-mentioned range, the leakage current density when an electric field of 250 kV / cm is applied to the KNN film 3 in the thickness direction is 500 μA / cm 2 Less than or equal to 250 μA / cm 2 Less than 200 μA / cm, more preferably 2 It can be the following:
[0031] Furthermore, for example, by setting the total concentration of Cu and Mn in the KNN film 3 within the above range, it is possible to set the relative dielectric constant of the KNN film 3 measured under conditions of a frequency of 1 kHz and ±1 V to 1500 or less, preferably 300 to 1200. If the relative dielectric constant of the KNN film 3 is within the above range, there is a tendency that the sensitivity of the piezoelectric laminate 10 is not likely to decrease when it is applied to, for example, a sensor. One of the reasons for this is thought to be that the amounts of Cu and Mn added are appropriate, and the crystals constituting the KNN film 3 can be preferentially oriented in the (001) plane direction with respect to the surface of the substrate 1.
[0032] By adding Cu to the KNN film 3 within the above-mentioned concentration range, this Cu pairs with the oxygen vacancies on the grain boundaries of the KNN film 3, i.e., the Cu on the grain boundaries traps the oxygen vacancies. As a result, it is possible to suppress the movement of oxygen vacancies on the grain boundaries of the KNN film 3.
[0033] Furthermore, by adding Cu to the KNN film 3 within the above-mentioned concentration range, in addition to improving the above-mentioned film characteristics, it is also possible to increase resistance (etching resistance) to a fluorine-based etching solution (for example, a buffered hydrofluoric acid (BHF) solution containing hydrogen fluoride (HF) and ammonium fluoride (NH4F) at predetermined concentrations). This eliminates the need to form a protective film to protect the exposed surface of the KNN film 3. In other words, it becomes possible to use a BHF solution as an etching solution without forming a protective film. As a result, the processing process in the treatment after forming the piezoelectric stack 10 can be simplified.
[0034] The KNN film 3 may contain elements other than K, Na, Nb, Cu, and Mn, such as lithium (Li), Ta, and antimony (Sb), at a concentration that allows the standard deviation of the KNN film 3 to be maintained within the above-mentioned range, for example, at a concentration of 5 at % or less.
[0035] The upper electrode film 4 can be formed using various metals such as Pt, Au, aluminum (Al), Cu, etc., or alloys thereof. The upper electrode film 4 can be formed using a method such as a sputtering method, a vapor deposition method, a plating method, a metal paste method, etc. The upper electrode film 4 does not have a large effect on the crystal structure of the KNN film 3, unlike the lower electrode film 2. Therefore, the material, crystal structure, and film formation method of the upper electrode film 4 are not particularly limited. Note that, in order to increase the adhesion between the KNN film 3 and the upper electrode film 4, an adhesion layer mainly composed of, for example, Ti, Ta, TiO2, Ni, etc. may be provided. The thickness of the upper electrode film 4 can be, for example, 10 to 5000 nm, and when an adhesion layer is provided, the thickness of the adhesion layer can be, for example, 1 to 200 nm.
[0036] (2) Piezoelectric device configuration 3 shows a schematic diagram of a device 30 having a KNN film 3 (hereinafter also referred to as a piezoelectric device 30) in this embodiment. The piezoelectric device 30 includes at least an element 20 (element 20 having a KNN film 3, hereinafter also referred to as a piezoelectric element 20) obtained by forming the above-mentioned piezoelectric laminate 10 into a predetermined shape, and a voltage application unit 11a or a voltage detection unit 11b connected to the piezoelectric element 20. The voltage application unit 11a is a means for applying a voltage between the lower electrode film 2 and the upper electrode film 4 (between the electrodes), and the voltage detection unit 11b is a means for detecting a voltage generated between the lower electrode film 2 and the upper electrode film 4 (between the electrodes). Various known means can be used as the voltage application unit 11a and the voltage detection unit 11b.
[0037] By connecting the voltage application unit 11a between the lower electrode film 2 and the upper electrode film 4 of the piezoelectric element 20, the piezoelectric device 30 can function as an actuator. By applying a voltage between the lower electrode film 2 and the upper electrode film 4 by the voltage application unit 11a, the KNN film 3 can be deformed. This deformation action can operate various members connected to the piezoelectric device 30. In this case, examples of applications of the piezoelectric device 30 include a head for an inkjet printer, a MEMS mirror for a scanner, and a vibrator for an ultrasonic generator.
[0038] By connecting the voltage detection unit 11b between the lower electrode film 2 and the upper electrode film 4 of the piezoelectric element 20, the piezoelectric device 30 can function as a sensor. When the KNN film 3 deforms in response to a change in some physical quantity, a voltage is generated between the lower electrode film 2 and the upper electrode film 4 due to the deformation. By detecting this voltage with the voltage detection unit 11b, the magnitude of the physical quantity applied to the KNN film 3 can be measured. In this case, examples of applications of the piezoelectric device 30 include an angular velocity sensor, an ultrasonic sensor, a pressure sensor, and an acceleration sensor.
[0039] (3) Methods for manufacturing piezoelectric laminates, piezoelectric elements, and piezoelectric devices Hereinafter, methods for manufacturing the above-mentioned piezoelectric stack 10, piezoelectric element 20, and piezoelectric device 30 will be described.
[0040] First, a substrate 1 is prepared, and an adhesion layer 6 (Ti layer) and a lower electrode film 2 (Pt film) are formed in this order by, for example, a sputtering method on either of the main surfaces of the substrate 1. Note that a substrate 1 on which the adhesion layer 6 and the lower electrode film 2 have been formed in advance on either of the main surfaces may be prepared.
[0041] The conditions for forming the adhesion layer 6 are exemplified as follows. Temperature (substrate temperature): 100°C or higher and 500°C or lower, preferably 200°C or higher and 400°C or lower Discharge power: 1000W or more and 1500W or less, preferably 1100W or more and 1300W or less Atmosphere: Argon (Ar) gas atmosphere Ambient pressure: 0.1 Pa or more and 0.5 Pa or less, preferably 0.2 Pa or more and 0.4 Pa or less Time: 30 seconds or more and 3 minutes or less, preferably 30 seconds or more and 2 minutes or less
[0042] The conditions for forming the lower electrode film 2 are exemplified as follows. Film-forming temperature (substrate temperature): 100°C or higher and 500°C or lower, preferably 200°C or higher and 400°C or lower Discharge power: 1000W or more and 1500W or less, preferably 1100W or more and 1300W or less Film deposition atmosphere: Ar gas atmosphere Ambient pressure: 0.1 Pa or more and 0.5 Pa or less, preferably 0.2 Pa or more and 0.4 Pa or less Film formation time: 3 to 10 minutes, preferably 4 to 7 minutes
[0043] Next, the KNN film 3 is formed on the lower electrode film 2 by, for example, a sputtering method. In forming the KNN film 3, the initial film formation speed is set to be faster than the later film formation speed. The composition ratio of the KNN film 3 can be adjusted, for example, by controlling the composition of the target material used in the sputtering film formation. The target material can be prepared by mixing and firing K2CO3 powder, Na2CO3 powder, Nb2O5 powder, Cu powder (or CuO powder, Cu2O powder), MnO powder, etc. The composition of the target material can be controlled by adjusting the mixing ratio of K2CO3 powder, Na2CO3 powder, Nb2O5 powder, Cu powder (or CuO powder, Cu2O powder), and MnO powder.
[0044] The following conditions are exemplified as conditions for forming the KNN film 3. The film formation time is appropriately set depending on the thickness of the KNN film 3 to be formed. Film-forming temperature (substrate temperature): 500°C or higher and 700°C or lower, preferably 550°C or higher and 650°C or lower Discharge power: 2000W or more and 2400W or less, preferably 2100W or more and 2300W or less Film deposition atmosphere: Ar gas + oxygen (O2) gas atmosphere Ambient pressure: 0.2 Pa or more and 0.5 Pa or less, preferably 0.2 Pa or more and 0.4 Pa or less Partial pressure of Ar gas relative to O gas (Ar / O partial pressure ratio): 30 / 1 to 20 / 1, preferably 27 / 1 to 23 / 1 Initial stage of film formation: the period from the start of film formation (0 min) to 5 min, preferably from the start of film formation to 3 min Late film production: The period after the early film production Initial film formation speed: More than 2 μm / hr and 6 μm / hr, preferably 3 μm / hr or more and 5 μm / hr or more Late film formation speed: 0.5 μm / hr or more and 2 μm / hr or less, preferably 0.5 μm / hr or more and 1.5 μm / hr or less, more preferably 0.5 μm / hr or more and 1 μm / hr or less
[0045] Then, the upper electrode film 4 is formed on the KNN film 3 by, for example, a sputtering method. The conditions for forming the upper electrode film 4 can be the same as those for forming the lower electrode film 2. As a result, a piezoelectric stack 10 having the substrate 1, the lower electrode film 2, the KNN film 3, and the upper electrode film 4 as shown in FIG.
[0046] Then, by forming this piezoelectric laminate 10 into a predetermined shape by etching or the like, a piezoelectric element 20 as shown in FIG. 3 is obtained, and by connecting a voltage application unit 11a or a voltage detection unit 11b to the piezoelectric element 20, a piezoelectric device 30 is obtained.
[0047] (4) Effects Obtained by the Present Embodiment According to this embodiment, one or more of the following advantages can be obtained.
[0048] (a) The standard deviation of the grain size of the crystals constituting the KNN film 3 is 0.42 μm or less, so that the life of the KNN film 3 can be extended. For example, when a highly accelerated life test (HALT) is performed, a KNN film 3 can be obtained in which the time until dielectric breakdown occurs is 10,000 seconds or more. In this specification, HALT is performed under the following conditions. First, a piezoelectric laminate 10 having the KNN film 3 is heated to a temperature of 200° C., and a positive or negative electric field of 300 kV / cm is applied to the upper electrode film 4. Then, the time (seconds) from the start of electric field application to dielectric breakdown under at least one electric field application condition (positive or negative electric field) is measured. In this embodiment, the leakage current density flowing through the KNN film 3 is 30 mA / cm 2 When this temperature was exceeded, it was determined that the KNN film 3 had reached dielectric breakdown.
[0049] The inventors of the present application performed HALT under the above conditions for each of Samples 1 to 5 of the KNN film 3 having a standard deviation of 0.42 μm. Each of Samples 1 to 5 was produced under the same conditions within the above range described in the above embodiment. The HALT measurement results were Sample 1: 15069 seconds, Sample 2: 15789 seconds, Sample 3: 19749 seconds, Sample 4: 16869 seconds, and Sample 5: 10286 seconds. The above HALT values are the averages of values measured at seven points within 0.5 mmφ for each sample.
[0050] (b) By having the standard deviation of the KNN film 3 be less than 0.30 μm, it is possible to obtain a KNN film 3 in which the time until dielectric breakdown is 19,000 seconds or more when HALT is performed under the above-mentioned conditions. Also, by having the standard deviation of the KNN film 3 be less than 0.30 μm, it is possible to obtain a KNN film 3 in which the time until dielectric breakdown is 20,000 seconds or more when HALT is performed under the above-mentioned conditions.
[0051] The inventors of the present application performed HALT under the above conditions for each of Samples 6 to 11 of the KNN film 3, which has a standard deviation of less than 0.30 μm (for example, about 0.29 μm). Each of Samples 6 to 11 was produced under the same conditions within the above range described in the above embodiment. The HALT measurement results were Sample 6: 25,920 seconds, Sample 7: 31,166 seconds, Sample 8: 44,126 seconds, Sample 9: 31,834 seconds, Sample 10: 32,657 seconds, and Sample 11: 19,131 seconds. The above HALT values are the averages of values measured at seven points within 0.5 mmφ for each sample.
[0052] In contrast, the inventors of the present application have confirmed that if the standard deviation of the KNN film 3 exceeds 0.42 μm, when HALT is performed under the above-mentioned conditions, it is not possible to obtain a KNN film 3 having a time until dielectric breakdown of 10,000 seconds or more.
[0053] (c) When depositing the KNN film 3, the initial deposition rate is made faster than the later deposition rate, so that the crystal nuclei constituting the KNN film 3 can be formed densely and uniformly on the lower electrode film 2, and the crystal grains constituting the KNN film 3 can be made uniform in size. As a result, the standard deviation of the KNN film 3 can be made 0.42 μm or less.
[0054] (d) By setting the average grain size of the KNN film 3 to, for example, 0.1 μm or more and 1.0 μm or less, it is possible to reduce the grain boundary density of the KNN film 3 while setting the standard deviation of the KNN film 3 to 0.42 μm or less. As a result, it is possible to reliably obtain the KNN film 3 in which the time until dielectric breakdown occurs is 10,000 seconds or more when HALT is performed under the above-mentioned conditions.
[0055] (e) By adding Cu to the KNN film 3, it is possible to suppress the movement of oxygen vacancies on the grain boundaries of the KNN film 3. As a result, oxygen vacancies in the KNN film 3 are less likely to reach the electrode film, which makes it possible to further extend the life of the KNN film 3.
[0056] (f) The inventors of the present application have confirmed that even when Mn is added to the KNN film 3, the standard deviation of the KNN film 3 is 0.42 μm or less, and therefore HALT results similar to those obtained when Cu is added to the KNN film 3. However, the addition of Cu to the KNN film 3 is more preferable than the addition of Mn in that it is possible to obtain the above-mentioned oxygen vacancy migration suppression effect and the effect of increasing the etching resistance of the KNN film 3.
[0057] <Other embodiments> Although the embodiment of the present invention has been specifically described above, the present invention is not limited to the above embodiment and can be modified in various ways without departing from the gist of the present invention.
[0058] The piezoelectric stack 10 does not necessarily have to include the lower electrode film 2. The piezoelectric stack 10 may be configured to include a substrate 1, a KNN film (piezoelectric film) 3 formed on the substrate 1, and an upper electrode film 4 (electrode film 4) formed on the KNN film 3. Even in this case, the same effect as in the above embodiment can be obtained by making the standard deviation of the KNN film 3 equal to or less than 0.42, preferably less than 0.30 μm.
[0059] By depositing a KNN film 3 on a substrate 1 having an adhesive layer 6 and depositing an electrode film 4 on the KNN film 3, a piezoelectric stack 10 (hereinafter also referred to as a piezoelectric stack 10A) without a lower electrode film 2 as shown in Fig. 4 can be obtained. The conditions for depositing (forming) each film (layer) can be the same as the conditions for each film (layer) shown in the above-mentioned embodiment. Note that the piezoelectric stack 10A does not need to have an adhesive layer 6.
[0060] In the piezoelectric laminate 10A, by setting the initial deposition rate faster than the later deposition rate when depositing the KNN film 3, the crystal nuclei constituting the KNN film 3 can be formed densely and with uniform size on the substrate 1 (adhesion layer 6). As a result, the crystal grains constituting the KNN film 3 can be made uniform in size, and the standard deviation of the KNN film 3 can be within the above-mentioned range.
[0061] 5 shows a schematic diagram of a piezoelectric device 30A fabricated using the piezoelectric laminate 10A. The piezoelectric device 30A is configured to include at least a piezoelectric element 20A obtained by forming the piezoelectric laminate 10A into a predetermined shape, and a voltage application unit 11a and a voltage detection unit 11b connected to the piezoelectric element 20A. In this embodiment, the piezoelectric element 20A has pattern electrodes formed by forming the electrode film 4 into a predetermined pattern. For example, the piezoelectric element 20A has a pair of positive and negative pattern electrodes 4p1 on the input side and a pair of positive and negative pattern electrodes 4p2 on the output side. An example of the pattern electrodes 4p1 and 4p2 is an interdigital transducer (abbreviated as IDT).
[0062] By connecting the voltage application unit 11a between the pattern electrodes 4p1 and the voltage detection unit 11b between the pattern electrodes 4p2, the piezoelectric device 30A can function as a filter device such as a surface acoustic wave (SAW) filter. By applying a voltage between the pattern electrodes 4p1 by the voltage application unit 11a, a SAW can be excited on the surface of the KNN film 3. The frequency of the excited SAW can be adjusted, for example, by adjusting the pitch of the pattern electrode 4p1. For example, the shorter the pitch of the IDT as the pattern electrode 4p1, the higher the frequency of the SAW, and the longer the pitch, the lower the frequency of the SAW. Of the SAWs excited by the voltage application unit 11a and propagating through the KNN film 3 to reach the pattern electrodes 4p2, a SAW having a predetermined frequency (frequency component) determined according to the pitch of the IDT as the pattern electrode 4p2 generates a voltage between the pattern electrodes 4p2. By detecting this voltage with the voltage detector 11b, it is possible to extract a SAW having a predetermined frequency from among the excited SAWs. Note that the term "predetermined frequency" used here may include not only a predetermined frequency but also a predetermined frequency band whose center frequency is a predetermined frequency.
[0063] For example, an orientation control layer for controlling the orientation of the crystals constituting the KNN film 3 may be provided between the lower electrode film 2 and the KNN film 3, that is, directly below the KNN film 3. When the lower electrode film 2 is not provided, the orientation control layer may be provided between the substrate 1 and the KNN film 3. The orientation control layer is, for example, a metal oxide such as SRO, LNO, strontium titanate (SrTiO3, abbreviation: STO), etc., and can be formed using a material different from the material constituting the lower electrode film 2. The crystals constituting the orientation control layer are preferably preferentially oriented in the (100) plane with respect to the surface of the substrate 1.
[0064] For example, in addition to Cu, or instead of Cu, the KNN film 3 may contain another metal element having the same effect as Cu at a concentration that can make the relative permittivity of the KNN film 3 an appropriate size while obtaining the above-described oxygen deficiency migration suppression effect. Even in this case, the same effects as those of the above-described embodiments can be obtained.
[0065] For example, when forming the above-described piezoelectric laminates 10, 10A into piezoelectric elements 20, 20A, as long as the piezoelectric devices 30, 30A manufactured using the piezoelectric laminates 10, 10A (piezoelectric elements 20, 20A) can be applied to desired uses such as sensors or actuators, the substrate 1 may be removed from the piezoelectric laminates 10, 10A.
[0066] <Preferred Embodiment of the Present Invention> Hereinafter, preferred embodiments of the present invention will be appended.
[0067] (Appended Note 1) According to one embodiment of the present invention, a substrate, an electrode film, a piezoelectric film made of an alkaline niobate oxide having a perovskite structure represented by the composition formula (K 1-x Na x ) NbO3 (0 <x <1), and a piezoelectric laminate is provided in which the standard deviation of the particle size of the crystals constituting the piezoelectric film is 0.42 μm or less, preferably less than 0.30 μm.
[0068] (Appendix 2) The piezoelectric laminate of Appendix 1, preferably, When a positive or negative electric field of 300 kV / cm is applied to the electrode film provided on the piezoelectric film at a temperature of 200 °C, the leakage current density flowing through the piezoelectric film from the start of the electric field application under at least one of the electric field application conditions is 30 mA / cm 2 The time until it exceeds is 10,000 seconds or more, preferably 19,000 seconds or more, more preferably 20,000 seconds or more.
[0069] (Appendix 3) The piezoelectric laminate of Appendix 1 or 2, preferably, The average particle size of the crystals constituting the piezoelectric film is 0.1 μm or more and 1.0 μm or less, preferably 0.3 μm or more and 0.5 μm or less.
[0070] (Appendix 4) The piezoelectric laminate according to any one of Appendices 1 to 3, preferably, The piezoelectric film contains a metal element selected from the group consisting of copper (Cu) and manganese (Mn) at a concentration of 0.2 at% or more and 2.0 at% or less.
[0071] (Appendix 5) The piezoelectric laminate of Appendix 4, preferably, The metal element is copper (Cu).
[0072] (Appendix 6) According to another aspect of the present invention, A substrate, A lower electrode film formed on the substrate, A piezoelectric film formed on the lower electrode film and composed of an alkali niobate oxide having a perovskite structure represented by the composition formula (K 1-x Na x )NbO3 (0 <x <1), An upper electrode film formed on the piezoelectric film, and A piezoelectric element (piezoelectric device) is provided in which the standard deviation of the particle size of the crystals constituting the piezoelectric film is 0.42 μm or less, preferably less than 0.30 μm.
[0073] (Appendix 7) According to still another aspect of the present invention, a substrate, a piezoelectric film formed on the substrate and composed of an alkali niobate oxide having a perovskite structure represented by the composition formula (K 1-x Na x )NbO3 (0 < x < 1), and an electrode film formed on the piezoelectric film, are provided. A piezoelectric element (piezoelectric device) is provided in which the standard deviation of the grain size of the crystal constituting the piezoelectric film is 0.42 μm or less, preferably less than 0.30 μm.
[0074] (Appendix 8) According to still another aspect of the present invention, a step of forming an electrode film on a substrate, and a step of forming a piezoelectric film composed of an alkali niobate oxide having a perovskite structure represented by the composition formula (K 1-x Na x )NbO3 (0 < x < 1) on the electrode film, are included. In the step of forming the piezoelectric film, a method for manufacturing a piezoelectric laminate is provided in which the initial film formation rate is made faster than the later film formation rate.
[0075] (Appendix 9) According to still another aspect of the present invention, a step of forming a piezoelectric film composed of an alkali niobate oxide having a perovskite structure represented by the composition formula (K 1-x Na x )NbO3 (0 < x < 1) on a substrate, is included. In the step of forming the piezoelectric film, a method for manufacturing a piezoelectric laminate is provided in which the initial film formation rate is made faster than the later film formation rate.
[0076] (Appendix 10) The method according to Appendix 8 or 9, preferably, the initial film formation rate is more than 2 m / hr and 6 m / hr or less, and the later film formation rate is 0.5 μm / hr or more and 2 μm / hr or less.
Explanation of symbols
[0077] 1 Board 3. Piezoelectric film 10 Piezoelectric laminate
Claims
1. A substrate; An electrode film; Composition formula (K 1-x Na x ) NbO 3 and a piezoelectric film made of an alkali niobium oxide having a perovskite structure represented by (0<x<1), The average grain size of the crystals constituting the piezoelectric film is 0.3 μm or more and 0.5 μm or less, A piezoelectric laminate, wherein the standard deviation of grain size of crystals constituting the piezoelectric film is greater than 0 μm and less than 0.3 μm.
2. 2. The piezoelectric laminate according to claim 1, wherein the piezoelectric film contains a metal element selected from the group consisting of copper and manganese at a concentration of 0.2 at % or more and 2.0 at % or less.
3. A substrate; A lower electrode film formed on the substrate; A film having the composition formula (K 1-x Na x ) NbO 3 a piezoelectric film made of an alkali niobium oxide having a perovskite structure represented by (0<x<1); an upper electrode film formed on the piezoelectric film; The average grain size of the crystals constituting the piezoelectric film is 0.3 μm or more and 0.5 μm or less, A piezoelectric element, wherein the standard deviation of the grain size of crystals constituting the piezoelectric film is greater than 0 μm and less than 0.3 μm.
4. forming an electrode film on a substrate; On the electrode film, a composition formula (K 1-x Na x ) NbO 3 forming a piezoelectric film made of an alkali niobium oxide having a perovskite structure represented by (0<x<1); In the step of depositing the piezoelectric film, the substrate temperature is 500° C. or higher and 700° C. or lower, the discharge power is 2000 W or higher and 2400 W or lower, the deposition atmosphere is a mixed gas atmosphere of argon gas and oxygen gas, the atmospheric pressure is 0.2 Pa or higher and 0.5 Pa or lower, the partial pressure of argon gas relative to oxygen gas is 30 / 1 to 20 / 1, the initial deposition rate is more than 2 μm / hr and 6 μm / hr or lower, and the later deposition rate is 0.5 μm / hr or higher and 2 μm / hr or lower.
Citation Information
Patent Citations
Piezoelectric laminate, surface acoustic wave device, thin-film piezoelectric resonator, and piezoelectric actuator
JP2007184513A
Piezoelectric thin film element, and actuator and sensor manufactured by using piezoelectric thin film element
JP2008159807A
Piezoelectric thin film-attached laminate board, piezoelectric thin-film device and manufacturing method thereof
JP2017076730A